Analysis of Speech Anxiety among EFL Learners in Japan: A Comparison - Muhammad Nur Adilin, Mohd Anuardi; Wan Noor Farah, Wan Shamsuddin; Atsuko K., Yamazaki (IJLT, 2023)
Due to the high encouragement from the Japan Ministry of Education, Culture, Sports, Science, and Technology (MEXT) to promote more internationalization among Japanese graduates, many higher education institutions have started introducing more communicative courses such as public speaking and presentation skills. These goals not only aim to ameliorate students’ communication skills, but also to foster global human resources. Although considerable research has been conducted on students’ communication skills, few have explored the causes of speech anxiety among university students, especially in the context of English as a Foreign Language (EFL). Thus, this study aims to fill this gap by analyzing 43 university students in Tokyo, Japan. According to the results, a pivotal link between gender and speech anxiety was found. Specifically, the female students exhibited higher public speaking anxiety, compared to the male students. This study also investigated the sources of speech anxiety in four domains: communicative apprehension, fear of negative evaluation, test anxiety, and general anxiety of English. Among all four components, the EFL students recorded the highest anxiety in communication apprehension. It is also interesting to note that after completing the presentation skills course, the female students showed a significant reduction in the fear of negative evaluation domain. It is hoped that the findings of this study will be used by instructors to improve EFL students’ communication skills.